‘Single’ v ‘panel’ appointed forensic mental observations: Is the referral process ethically justifiable - Tiaan Schutte; Ugasvaree Subramaney (South African Journal of Bioethics and Law, 2013)
Objective. This study compares the outcome and psychiatric morbidity of the forensic mental observation referrals, in the two legally created groups of detainees awaiting trial – the ‘singles’, representing the minor violent and non-violent offenders evaluated by a single-state appointed psychiatrist, v. the ‘panels’, representing the seriously violent offenders evaluated by two or more psychiatrists.Methods. A retrospective record review covered 200 cases, comprising all individuals admitted to the forensic unit of Sterkfontein Hospital for 30 days psychiatric observation from January to August 2010. Pearson’s χ2 test for categorical data was used to determine statistical significance.Results. Of 110 singles, 49 (44.55%) were found fit for trial and 40 (40.4%) were found criminally responsible. Of the 90 ‘panel’ cases 60 (66.67%) were found fit for trial and 57 (64.77%) were found criminally responsible (p=0.002 and p=0.001, respectively)Conclusion. Those charged with seriously violent offences appear more likely to be found both fit and responsible, compared with those charged with less serious offences.